Utilização de DDG e torta de girassol na alimentação de bovinos e ovinos confinados - Rufino Junior, João (2017)
In this research two experiments were carried out to evaluate the use of by products in confined ruminant feed. In the experiment 1, the objective of this study was to evaluate increasing levels of inclusion of DDG in soybean meal replacement (zero, 25, 50, 75 and 100%) in the diet of beef cattle in confinement. For this experiment 25 animals were used Nelore, uncastrated males with average initial weight of 30.84 kg +364.08 distributed in five treatments in a completely randomized design. We evaluated the intake and digestibility of dry matter and nutrients. The performance of the animals was also evaluated through the following variables: carcass yield; total weight gain; average daily gain; carcass gain; gain yield; feed conversion; feed efficiency and economic viability .The substitution of soybean meal by DDG not significant (P> 0.05) in mean daily dry matter intake, with an average of 9.15 kg. The soybean meal replacement DDG promoted by a linear decrease (P <0.035) in the non-fibrous carbohydrate consumption. However, they resulted in a linear increase (P <0.05) for the digestible neutral detergent fiber. When contrasted with treatments include DDG and DDG no significant differences (P> 0.03) for the GC variable, having a higher gain for the treatment without adding DDG. The treatment with greater substitution of soybean meal, 100%, presented greater economic viability. In the experiment 2, the objective was to evaluate the intake, digestibility and ingestive behavior of sheep submitted to diets with increasing levels of sunflower cake. For this experiment we used four lambs in a desing in latin square 4x4, which were submitted to the sunflower cake levels of zero, 10, 20 and 30% in the diet. The inclusion levels of sunflower cake didn’t influence (P> 0.05) the values of dry matter intake (CMS) in absolute values and in percentage of body weight (% PC). The inclusion of sunflower cake in the confined sheep feed did not influence (P> 0.05) the apparent digestibility of dry matter, organic matter and mineral matter. The average time of rumination and idle differ linearly (P <0.05) increased with the inclusion of sunflower cake. But the time spent fedding was not affected. With the increase of the inclusion of sunflower cake increased the rumination time and decreased the idle time of the animals. The inclusion of sunflower cake in the sheep diet has been shown to be a good alternative to include in the diet.